(untitled) (Research, Society and Development, 2019)
Gender, sexuality and diversity at school still seem to be distant concepts from reality, leading to situations of exclusion and prejudice in the school environment. Thus, this article aims at identifying and analyzing the teachers’ beliefs and perceptions within the context of the Federal Institute of Northern Minas Gerais, Salinas campus, regarding sexuality and gender issues. In order to do so, we have based on the results of a research project that analyzed the teachers’ conceptions about these concepts at the campus. The methodological approach was held by qualitative and quantitative research. Electronic questionnaires were made available for all teachers of the mentioned campus for data collection. Furthermore, the results showed that most of the teachers do not receive prior orientation to tackle these issues and thus, there is the necessity to build an inclusive and multidimensional pedagogical practice. Hence, we believe the research has contributed to show the importance of the theme as well as identify prejudice and discriminatory practices regarding sexual diversity and gender present in the school environment.